ANALYSIS FF FACTORS AFFECTING PROFIT GROWTH OF CELLULAR TELECOMMNUNICATION OPERATOR COMPANIES ON THE INDONESIAN STOCK EXCHANGE - Rahmat, Burhan Irsali; Natsir, Khairina (Graduate Program of Universitas Tarumanagara, 2024)
A comparison will be made between the Current Ratio (CR), Net Profit Margin (NPM), and Return on Assets (ROA) in connection to the increase of profits in infrastructure-related cellular telecommunications operator enterprises (XL, Telkomsel, Smartfren, and Indosat) between the years 2016 and 2022. A number of tests are included in the research protocol. These tests are as follows: the Chi-Square test (CoW) for selecting a common effect model, the likelihood ratio test (LM) for selecting a random effect model, the Breusch-Pagan test for detecting heteroscedasticity, the Multicollinearity test for identifying multicollinearity, the regression test with the common effect model (CEM) for determining the effect of independent variables on earnings growth, and the coefficient of determination test for determining the ability of CR, NPM, and ROA to explain earnings growth variability. The data indicates that the activities of mobile telecom operator enterprises operating within the infrastructure sector had a positive influence on the increase of profits derived from CR, NPM, and ROA. In accordance with the results of the LM test, the Common Effect Model is more appropriate than the Random Effect Model. In addition, the Breusch-Pagan test shows the absence of heteroscedasticity in the model. Multicol test also confirmed the absence of multicollinearity problem in the analysis. This study provides important insights into the factors that influence earnings growth in the mobile telecommunications industry in the infrastructure sector. These results can assist company management in designing more effective financial strategies to achieve better earnings growth.